Development of indoor positioning system by using phone equipped sensors - Lu, Yunfan (2017)
In recent decades, mobile devices have made its way into people’s daily lives provided countless benefits. One valuable function that mobile devices offer is providing location services to users. Although in outdoor environment, satellite based GPS system has proven to provide relatively reliable and accurate location services, such location service in indoor environment remains a challenge due to the lack of direct transmission channels between GPS satellite and receivers. Among various alternative technologies, WIFI localization has the advantage of being the most convenient and low-cost solution because it can easily make use of existing infrastructure and is praised as being the cheapest solution. However, WIFI often suffers the problem of having poor accuracy and parsimonious delay. To overcome the limitations of WIFI, we made use of the data collected by Inertia Measurement Unit(IMU) and fused WIFI measurement with position prediction calculated by smartphone-based pedestrian dead reckoning algorithm (PDR) using particle filter. An android application is developed to evaluate the performance of the proposed approach in real environment.